PARAVERBAL ORGANIZATION OF FEMALE POLITICAL DISCOURSE IN SPAIN, LATIN AMERICA AND UKRAINE (a contrastive perspective based on an audiovisual approach) - В. О. Чернякова (Записки з романо-германської філології, 2016)
This paper aims at studying the paraverbal organization of female political discourse in Spain, Latin America and Ukraine based on public speeches delivered by female Spanish-speaking (Eva Peron, Cristina de Kirchner, Manuela Carmena) and Ukrainian-speaking (Yulia Timoshenko, Lesya Orobets, Irina Farion) public figures. The article summarizes theoretical approaches to the study of gender-specific female speech, lingual and prosodic features of Hispanic and Ukrainian female political discourse, and means of female expressiveness explicated in vocabulary, prosody, and co-speech gestures. Contrastive audio-visual processing using PRAAT 5.0.43 and Sound Forge 9.0 software revealed similarities and contrasts in prosodic and kinetic female expressiveness in Spanish, Latin American and Ukrainian political discourses. The study allowed validating the hypothesis that contrastive verbal and paraverbal (prosodic and kinetic) features of female political speech are typologically specific for Spanish and Ukrainian languages. On the other hand, the integral features of female speech in Spanish, Latin American and Ukrainian linguistic cultures are determined by the persuasive specifics of political discourse and are explicated in common rhetorical tools, discursive strategies and tactics used by women to achieve maximum impact on the audience in any linguistic culture of any genetic affinity.